Protein interaction with glycocalyx-mimetic surfaces: a candidate for blood-compatible materials - Hedayati, Mohammadhasan, author; Krapf, Diego, author; Kipper, Matt J., author (Colorado State University. Libraries, 2017)
Biomaterials and medical devices induce tissue responses when they get into contact with human blood and rapidly becomes covered with a layer of nonspecifically adsorbed proteins. For blood contacting devices, protein adsorption is undesirable and is generally the first event in blood coagulation. The polymer coating on solid surfaces is an efficient approach for modification of materials to design protein resistant biomaterials. The aim of this work is to mimic the endothelial glycocalyx layer on the surface of blood vessels, which is responsible for anticoagulant activity by restricting molecules such as proteins from reaching the endothelium.
128 - Mohammadhasan Hedayati